Appearance of the emarate of kermani in Anatolia(634-728ah)-(1327-1236 ad) - Omar, Othman A. (Humanities Journal of University of Zakho, 2016)
This study aims to shed the light on the Karamanid's family ancestry and the stages of emergence of the role of Karamanid's princes in Anatolia in the mid of 7th/13th AD centuries. The land of Seljuk State in Asia Minor was exposed by the Mongol invasion and even after the fall of the Seljuk state year (704 AH / 1304 AD). The top Karamanid's princes were actually come out during the Mongol domination on Asia Minor, as those princes who took the advantage of the weakness of the central authority in Konya, especially in the recent Seljuk state who have declared their subordination to the Mongols time, even they started to construct the largest opposition force politically and militarily against the Mughal individuals, and mostly is the threat to the interests of the Mongol in Anatolia, after they unified their forces against the Mughal rule and refused to pay the imposed taxies of the disputed areas to Mongols authority, the Turkmen princes encouraged to be the anti-Mongol rules, who sent the powerful kings to Egypt in order to establish a political and military relationship with them for the expulsion of the Mongols from Asia Minor after belittling the role of Roman Seljuks kings in Konya, furthermore, they supported the Mongol princes' movements in Anatolia, who have declared their rebellions against the Iranian Ilkhanid government and the independence from the rule of Ilkhanid in Tabriz, It did not hesitate the Karamanid's princes for exploiting any opportunities in order to strike the Mongols and weaken them, and exclude the country from their authority and access to the achievement of the independence in the areas where are under their influences. in addition, to establish the independent emirate for them with the political and military sovereignty away from deputed authorities and Mongolian leaders in the country and the majestic orders are incoming from the Roman Seljuks king in Konya until they have controlled Konya in a year (728 AH / 1328 AD).